Maize Lethal Necrosis (MLN) and its management - Prasanna, Boddupalli M.; Mahabaleswara, Suresh L. (Indian Council of Agricultural Research, 2023)
Maize lethal necrosis (MLN) is a major viral disease caused by a synergistic interaction of Maize Chlorotic Mottle Virus (MCMV) and Sugarcane Mosaic Virus (SCMV) or other potyviruses. The first outbreak of MLN in Kenya in 2011, followed by its rapid spread to several countries in eastern Africa within a span of 3-4 years, caused huge concern to stakeholders across the African continent. Rapid response and intensive multi-disciplinary and multi-institutional efforts by the International Maize and Wheat Improvement Center (CIMMYT) in partnership with an array of national and international institutions resulted in development and deployment of an array of tools/technologies to effectively tackle the MLN challenge. MLN is still prevalent in eastern Africa and has not been eradicated. The threat of the disease spreading to other regions in sub-Saharan Africa (e.g., southern Africa or West Africa) still looms. Therefore, it is important to continue implementing an integrated disease management approach for sustainable management of the disease in the MLN-prevalent countries whether in Africa, Americas or Asia, and continued efforts on MLN disease monitoring and surveillance globally. This Chapter provides an update on the disease and its management, including the causal viruses, especially MCMV and SCMV, their host range, symptoms, and conditions for development; modes of transmission of MLN-causing viruses; MLN diagnostics and surveillance; and approaches for sustainable management, particularly host plant resistance, MLN-free clean seed production and exchange, and agronomic management.